Public acceptance of national renewable energy policy among landed residents in Peninsular Malaysia - Mohd Sobri, Fatimah Azzahraa' (2022)
Policy goals for sustainable energy will be hampered without sufficient public acceptance. While there is a growing body of literature on public acceptance of solar energy, most studies tend to investigate public acceptance of new technology, not on the policies constructed to help the successful deployment of the technology. This research was conducted to identify public acceptance of solar-related items of the National Renewable Energy Policy among landed residents in Peninsular Malaysia and key factors contributing to the acceptance. The theoretical framework underlying this research follows Stern's Attitude- Behaviour-Context (ABC) framework that integrates attitudinal, contextual, and personal capability factors in one framework that is both comprehensive and feasible to undertake. These are personal norm, environmental concern, economic, social, roof position, certain socio-demographic factors, and home ownership. The study extends the ABC framework by proposing solar policy acceptance role as an antecedent to intention to adopt and information provision to increases policy acceptance. A survey design and an experimental design was conducted to achieve the research objectives. For the survey design, questionnaires with a 5-point Likert scale were distributed via multistage cluster systematic sampling to landed residents in Peninsular Malaysia (N=508) and analysed both descriptively and inferentially using Statistical Package for Social Science (SPSS) and Partial Least Square Structural Equation Modelling (PLS-SEM). The experimental design follows the Solomon Four Group Design where the data from four groups were analysed using a string of t-test analysis. The structural model analysis provides evidence of moderate model fit with R2 = 0.44 for policy acceptance and significant path relations for attitudinal variable (β= 0.342) and contextual variable (β=0.442) to policy acceptance. Several main findings that emerged were contextual factors, especially economic factors, prove more important than other factors and can be the focus for future solar policy decision-making. Another finding is the proof that policy acceptance (passive behaviour) can act as an antecedent to intention to adopt solar PV (active behaviour) at homes which shows the importance of the public to accept the National Renewable Energy Policy. Another conclusion was that policy information that is simple and appealing to the public can boost policy acceptance. Policy makers need to be aware that although both attitudinal and contextual factors are important for acceptance, certain contextual factors may carry more weight as a determinant for solar policy acceptance. The research is significant in extending the policy acceptance model by identifying unique variables to solar policy acceptance and the extension of intention to adopt solar PV after policy acceptance. It also provides more literature on the controversial Knowledge Deficit Model on the way information of the policy can be conveyed to affect solar policy acceptance. Lastly, the findings provide recent and essential data of the current acceptance and factors that interest the public so that policy makers can make informed decisions for future policy improvements.